Investigation on the effects of Glass Fibers over GGBS based Geopolymer Concrete under Ambient Curing - Chithambar Ganesh A.; Pream Kumar S.; Mukilan K.; Nandhini U.; Vijay Sankar K.; Sivagami N.; Jayapal D. (E3S Web of Conferences)
Fiber reinforced concrete as well as geopolymer concrete are contemporary developments in concrete arena. Incorporating fibers in geopolymer concrete would extend the applicability of geopolymer concrete in various fields. Hence in this study an effort has been made by introducing alkali resistant glass fibers in geopolymer concrete. The main objective is to investigate effect of glass fibers over geopolymer concrete with various proportions such as 0.25, 0.5, 0.75, 1 and 1.25 percentages. Geopolymer concrete is made of GGBS and hence ambient curing is implemented. Alkali solution is the combination of sodium hydroxide and sodium silicate solution in the ratio of 1:2.5. Geopolymer concrete is tested for fresh property such as workability, hardened property such as compressive strength and ultimate bond strength. The durability parameters are validated by water absorption, Rapid Chloride Penetration Test, Acid attack, sulphate attack and marine water attack. Results indicate better behavior of geopolymer concrete with incorporation of glass fibers. This study unleashes hefty possibility in reinforced geopolymer concrete arena.